2010
DOI: 10.1063/1.3467522
|View full text |Cite
|
Sign up to set email alerts
|

Surface preparation and homoepitaxial deposition of AlN on (0001)-oriented AlN substrates by metalorganic chemical vapor deposition

Abstract: Chemical surface treatments were conducted on mechanically polished (MP) and chemomechanically polished (CMP) (0001)-oriented single crystalline aluminum nitride (AlN) substrates to determine a surface preparation procedure for the homoepitaxial deposition of AlN epitaxial layers by metalorganic chemical vapor deposition. MP AlN substrates characterized by atomic force microscopy exhibited 0.5 nm rms roughness and polishing scratches, while CMP AlN substrates exhibited 0.1 nm rms roughness and were scratch-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 30 publications
0
74
0
Order By: Relevance
“…Improved surface processing will be critical for achieving high quality epitaxy on AlN. A recent study reported by Rice et al describes a procedure by which high quality AlN homoepitaxy can be obtained on properly CMP substrates [6]. Furthermore, studies of strain relaxation in AlGaN alloys grown on AlN are necessary to guide device design and ensure low defect densities are preserved in active heterostructure layers.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Improved surface processing will be critical for achieving high quality epitaxy on AlN. A recent study reported by Rice et al describes a procedure by which high quality AlN homoepitaxy can be obtained on properly CMP substrates [6]. Furthermore, studies of strain relaxation in AlGaN alloys grown on AlN are necessary to guide device design and ensure low defect densities are preserved in active heterostructure layers.…”
Section: Introductionmentioning
confidence: 98%
“…The selected precursors flow yielded a growth rate of 500 nm/hr with no observable pits on the surface. The structural quality of these films have been described elsewhere [6]. The AlGaN was deposited on that layer at a temperature of 1100 ºC by introducing the Ga precursor into the above described gas flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The root-mean-square (RMS) surface roughness of the AlN template is less than 0.10 nm and 0.12 nm, respectively, as determined by 1 Â 1 lm 2 and 5 Â 5 lm 2 AFM measurements, which are comparable to bulk AlN substrates. 16 Thus, the AlN template layer used herein provided a smooth surface for subsequent growth of AlGaN-based laser structures.…”
mentioning
confidence: 99%
“…As a result, high structural defect concentrations are commonly observed in heteroepitaxially grown films, seriously degrading the material quality [1,5]. AlN substrates appear as most promising alternative for the continuous evolution of nitride based optical devices towards the deep UV spectral range [6][7][8]. Consequently, not only the growth of AlGaN films with a high AlN concentration becomes feasible, but also ultimately homoepitaxial growth of AlN for device applications comes within reach.…”
Section: Introductionmentioning
confidence: 99%